Consideration of the energy efficiency class of a residential building in parametric pricing - Izmaylova, E. (Ways to Improve Construction Efficiency, 2019)
In Ukraine, new requirements for the design of buildings and structures are introduced, the basis of which are parametric design methods, that is, when not fixed fixed signs, sizes, norms are specified, but parameters that the project must meet. Today, there is a need to develop conceptual provisions for parametric pricing and to calculate individual parameters of buildings and structures on a new basis, among which the need to provide a given class of energy efficiency is particularly prominent. The purpose of the article is to substantiate the impact of the energy efficiency of a building on the market price of its implementation and to create appropriate dependencies on the basis of a widely known and well-tested method of correlation-regression analysis. The calculated regression equation for the dependence of the energy efficiency of a dwelling house on the set of engineering and technical design solutions: Twenty-seven variants of increasing the energy efficiency class of a house in the following main directions (factors of the model X1-xrodes): (various variants of wall insulation), thermal insulation of engineering communications, installation of modern windows and balcony doors, thermal insulation cons ruktsiy roof. Of these four factors, the most influential factor was X2 (thermal insulation of engineering communications), the least influential was X4 (thermal insulation of roof structures). The coefficient of determination of the obtained equation, which is equal to 0,888, shows that the impact of other factors on the level of energy efficiency that has been left out of the equation is only 11,2%. That is, the equation covers the lion’s share of the impact factors, so it can and should be used in assessing the impact of engineering solutions on the energy efficiency class. The dependence of the market price of the object on the level of its energy efficiency is determined, which can be used as a parametric series in pricing.